Penerapan Aromaterapi Levender Untuk Mengurangi Kecemasan Pada Lansia Berdasarkan Toeri Humanistik Watson Di Panti Sosial Tresna Werdha Provinsi Bengkulu Tahun 2025 - Deskia Tiara; Tita Septi Handayani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The elderly population in Indonesia is increasing, and several provinces have entered an ageing population structure. Anxiety is a mental health problem that often occurs in the elderly and can have an impact on physical and psychological health. Non-pharmacological treatment methods, such as aromatherapy, can be used as an alternative to reduce anxiety levels in the elderly. Objective: To understand and apply nursing care for the elderly to reduce anxiety using lavender aromatherapy based on Watson's humanistic theory at the Tresna Werdha Social Welfare Institution in Bengkulu Province.The research method used in this study was a case study, which was used to explore the application of lavender aromatherapy to reduce anxiety in the elderly based on Watson's humanistic theory. There were two participants in this study, both with the same case, namely nursing problems related to anxiety. The results of the study on client 1 and client 2 showed that in Case 1 and Case 2, the anxiety problem could be resolved, thus concluding that the application of lavender aromatherapy can reduce anxiety in the elderly.It is hoped that the Tresna Werdha Social Welfare Home can provide the best possible service and be able to apply this method easily and relatively inexpensively, with minimal side effects compared to pharmacological drugs